Digital Transformation: Best Practices of Educational Platform in Indonesia - Aini, Qurrotu; Kurniawan, Andy; Sulistiyowati, Tutur Bina (Jurnal Transformative, 2024)
The objective of this research is to scrutinize and offer a comprehensive perspective on the digital transformation in Indonesia’s educational system, along with exploring the factors that contribute to its success. The research employed a desk study approach, entailing a literature review and descriptive analysis methodology. The findings in this study reveal that the educational reform initiated by the Ministry of Education and Culture acts as a response to the Global Education Reform Movement (GERM). This reform is characterized by the adoption of the Merdeka curriculum and digital transformation, which involves technological interventions, launching various applications such as Arkas, SiPLah, Educational Report Cards and ‘Merdeka Belajar’. The technological intervention has exhibited a significant impact on users and has been in line with the defined objectives. The incorporation of technology in the educational system can streamline lengthy multi-level processes and expedite the dissemination of information. The Ministry of Education and Culture’s successful implementation of digital transformation has earned them numerous accolades both nationally and internationally. The key factors driving the success of this digital transformation include transformational leadership from the Minister of Education and Culture, school principals/teachers, the design and development process of the digital transformation that involves user engagement, and collaborative implementation.